The Role of Annealing Treatment on Crystallographic, Optical, and Electrical Features of Bi2O3 Thin Films Prepared Using Reactive Plasma Sputtering Technology - Sabeeha A. J. Beden; Hassan A. Dumboos; Mustafa K. Ismael; Mohanad Kadhim Mejbel (Journal of Nanotechnology)
Bismuth oxide (Bi2O3) has attracted considerable research interest in test thin films made utilizing the reactive plasma sputtering (RPS) technology-assisted annealing treatment, allowing the development of diverse BixOx thin films. SEM, phase X-ray diffraction patterns, UV-Vis spectrometers, and D.C. two-probes are used to identify the crystallographic structure and assess the films’ optical-electrical properties. The XRD examination showed that forming Bi2O3 films with an amorphous to multiphase crystalline structure for sputtering time of 40 min was due to soda glass substrate temperature at a range of 30–35°C. Thin films of Bi2O3 crystal structures improved with annealing heat treatment at 200, 300, 400, and 500°C. Yet the formation of crystalline phase (β-Bi2O3 with δ-Bi2O3) Bi2O3 nanostructures occurred at higher temperatures. SEM images showed transparent particles highly affected by annealing temperatures. The nanostructures were about 102–510 nm long, and the diameter was 50–100 nm. The Bi2O3 film optical band gaps and nanostructures ranged from 2.75 to 3.05 eV. The annealing temperature differences affected the crystallite sizes, optical band gaps, and surface roughness. The findings showed that these differences caused the phase transition in Bi2O3 structures. The electrical calculation revealed that the electrical conductivity improved with annealing temperatures of 150–250°C while declining with temperature (300–500)°C with typical semiconductor films.